Marketing esportivo no futebol: um olhar à luz do paradigma do marketing de relacionamento - Myskiw, Mauro (2006)
The relationship marketing is re-emerged with a potential for a new view of marketing. In a great part of business areas this approach has been researched, but in the sporting business there is a lack in which refers to this marketing paradigm. Because of this, it was decided by the research in soccer modality, for being this the biggest expression in the sporting business of Brazil, whose sporting spectacle nowadays is just possible in the intersection of relationship among clubs, administration entities, cheers, media, and investors, an imaginary organization here denominated of production nucleus of soccer product . And, knowing of the importance of the trust and the commitment as builders of relationship marketing, the aim of the work it was to know the factors who determine the commitment in the relationships between the agents of the soccer production nucleus. The research was in the kind of quali-quantitative, with an exploratory delineation. The data from the study were found in the relations established by the agents of the nucleus, by the occasion of the accomplishment of the Gaúcho Championship of Soccer. The sample selection was non probabilistic, in an intentional way, by convenience. Twenty two people took part of the sample, being: seven connected to the clubs, two to the Soccer Administration Entity, five to the Clubs Organized Cheers, five to the Sporting Media, and three to the investors. The data collection was done by semi-structured interview. The interviews were recorded and transcribed. The information were submitted to a contend analysis. In a first moment, they were done thematic pruning to compound the register unities and, later, these unities were disposed in categories and sub-categories. After the presentation and discussion of the results, it is concluded that the determined factors of the trust and commitment are objectives and functional in the case of the relationship between the Club and the Gaúcha Soccer Federation, Sporting Media and Investors. In these relationships, because of the factors nature, it can infer that the limits among the organizations are clearer and fixed, what would be justifying this kind of interaction. And, when it is mentioned about the relationship between the Club and the Cheers and between the Club and the Adversaries, the factors are linked to subjective and affective questions, on the development of future projects. In this case, the limits between the organizations and agents are more obscure, so they interpenetrate the subjectivity of parts, making with there is more complicity in the interactions.